Chronic Inflammatory Neuropathies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The clinical characteristics, response to therapy, and long-term prognosis in 13 children (1.5 to 16 years of age) with chronic inflammatory demyelinating polyneuropathy (CIDP) were reviewed from records of patients seen at Washington University Medical Center, St Louis, MO, and the Royal Children's Hospital, Melbourne, Australia, between 1979 and 1994.